1987
DOI: 10.1007/bf00016147
|View full text |Cite
|
Sign up to set email alerts
|

The relatively large beta-tubulin gene family of Arabidopsis contains a member with an unusual transcribed 5? noncoding sequence

Abstract: We have characterized the beta-tubulin gene family of Arabidopsis thaliana. Five distinct genes were cloned and analyzed by restriction enzyme mapping and cross-hybridization studies. Three of the genes appear to be dispersed, whereas two others are linked within 1.5 kb of one another. The two linked genes are closely related and appear to have resulted from a fairly recent duplication. The three dispersed genes do not cross-hybridize to one another or to the two linked genes under highly stringent hybridizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 42 publications
0
71
0
Order By: Relevance
“…Antibodies raised against SDS-PAGE purified plant tubulin monomers, as well as ligand binding studies, have shown that plant tubulins have some unique biochemical properties, but share many of the characteristics of the better characterized vertebrate tubulins (10). Analysis of the sequences of,B-tubulin genomic clones isolated from soybean (15) and from Arabidopsis thaliana (20,23) have demonstrated that plant tubulins are encoded by multi-gene families, and that they exhibit a high degree of sequence homology (over 80% at the amino acid level) with the tubulins of other eukaryotes, including mammals (6,27). Although relatively little is known about the factors regulating microtubule assem- bly in higher plant cells, given the high degree of similarity between eukaryotic tubulins, it is likely that the assembly process will be similar to that observed in mammalian cells where the assembled microtubules have been shown to be in a dynamic equilibrium with a pool of soluble tubulin dimers (18).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies raised against SDS-PAGE purified plant tubulin monomers, as well as ligand binding studies, have shown that plant tubulins have some unique biochemical properties, but share many of the characteristics of the better characterized vertebrate tubulins (10). Analysis of the sequences of,B-tubulin genomic clones isolated from soybean (15) and from Arabidopsis thaliana (20,23) have demonstrated that plant tubulins are encoded by multi-gene families, and that they exhibit a high degree of sequence homology (over 80% at the amino acid level) with the tubulins of other eukaryotes, including mammals (6,27). Although relatively little is known about the factors regulating microtubule assem- bly in higher plant cells, given the high degree of similarity between eukaryotic tubulins, it is likely that the assembly process will be similar to that observed in mammalian cells where the assembled microtubules have been shown to be in a dynamic equilibrium with a pool of soluble tubulin dimers (18).…”
Section: Discussionmentioning
confidence: 99%
“…Northern blot analysis was carried out as previously described (Smith et al, 2001) using an RT-PCR product amplified with primers BRK1-05 and BRK1-06 as a probe to detect BRK1 mRNA. To detect ␤-tubulin RNA, a 1.2 kb BamHI/EcoRI fragment of a ␤-tubulin cDNA clone isolated by Marks et al (Marks et al, 1987) was used as a probe. Radioactive hybridization signals were digitized using a Molecular Dynamics Phosphorimager, and signals quantitated using ImageQuant version 1.2 software.…”
Section: Rna Analysismentioning
confidence: 99%
“…Total DNA (20 g) digested with EcoRI (E), HindIII (H), BamHI (B), SacI (S), or XbaI (X) was subjected to gel electrophoresis followed by hybridization with a 32 P-labeled 1.5-kb cDNA fragment derived from the partial clone pBK-AtCAP16-1. (Marks et al, 1987) genes. (C) Total soluble protein (20 g) isolated from suspension-cultured cells (Cell susp.…”
Section: Isolation Of An Arabidopsis Cdna Encoding a Cap Homologmentioning
confidence: 99%